Transcriptome profiling of two rice genotypes under mild field drought stress during grain-filling stage. Issue 4 (5th July 2021) - Liang, Yuya; Tabien, Rodante E; Tarpley, Lee; Mohammed, Abdul R; Septiningsih, Endang M
Abstract: Drought is one of the most critical abiotic stresses that threaten crop production worldwide. This stress affects the rice crop in all stages of rice development; however, the occurrence during reproductive and grain-filling stages has the most impact on grain yield. Although many global transcriptomic studies have been performed during the reproductive stage in rice, very limited information is available for the grain-filling stage. Hence, we intend to investigate how the rice plant responds to drought stress during the grain-filling stage and how the responses change over time under field conditions. Two rice genotypes were selected for RNA-seq analysis: '4610', previously reported as a moderately tolerant breeding line, and Rondo, an elite indica rice cultivar susceptible to drought conditions. Additionally, 10 agronomic traits were evaluated under normal irrigated and drought conditions. Leaf tissues were collected during grain-filling stages at two time points, 14 and 21 days after the drought treatment, from both the drought field and normal irrigated field conditions. Based on agronomic performances, '4610' was less negatively affected than Rondo under mild drought conditions, and expression profiling largely aligned with the phenotypic data. The transcriptomic data indicated that, in general, '4610' had much earlier responses than its counterpart in mitigating the impact of drought stress. Several key genes and gene families related to drought stress or stress-related conditions were found differentially expressed in this study, including transcription factors, drought tolerance genes and reactive oxygen species scavengers. Furthermore, this study identified novel differentially expressed genes (DEGs) without function annotations that may play roles in drought tolerance-related functions. Some of the important DEGs detected in this study can be targeted for future research. Abstract : Few global transcriptomic studies have been performed in rice to study drought stress at the grain-filling stage. This study investigated drought stress responses of two rice genotypes using RNA-seq analysis at the grain-filling stage under drought and normal irrigated conditions. The transcriptomic data indicated that the moderately tolerant cultivar had significantly earlier responses than the susceptible cultivar in mitigating the impact of drought stress. Several key gene families were found differentially expressed, including transcription factors, drought tolerance genes and reactive oxygen species scavengers. This study also identified novel unannotated differentially expressed genes that can be investigated further.